Outdoor Activity in the Daytime, but Not the Nighttime, Predicts Better Mental Health Status During the COVID-19 Curfew in the United Arab Emirates - Al Anouti, Fatme; Thomas, Justin; Karras, Spyridon; El Asswad, Nour (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic and the associated infection prevention and control measures had a negative impact on the mental health of many people. In the United Arab Emirates (UAE), infection control measures implemented after March 24th, 2020 placed necessary restrictions on people’s freedom of movement, including the closure of recreational venues (lockdown) and the implementation of a nationwide curfew between the hours of 8pm and 6am. Aim: This study aimed to assess the association between levels of daytime versus nighttime outdoor activity and mental health among a sample of UAE residents during the lockdown period. Method: An opportunity sample of 245 participants completed an online survey assessing levels of depression, somatic symptoms, daytime and nighttime activity levels along with other questions pertaining to lifestyle habits. Results: Multivariate logistic regression revealed that daytime activity, but not nighttime activity, was associated with a lower risk of clinically significant depressive and somatic symptomatology. Conclusion: The association of better mental health with daytime but not nighttime outdoor activity could be possibly attributed to vitamin D, but further studies are needed before this speculation is confirmed.